2016
DOI: 10.1007/s00167-016-4331-7
|View full text |Cite
|
Sign up to set email alerts
|

No difference in range of motion between ultracongruent and posterior stabilized design in total knee arthroplasty: a randomized controlled trial

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 21 publications
4
34
0
Order By: Relevance
“…Many studies have compared between TKAs with an UC insert and other design inserts. 9,11 14,31,32 In terms of clinical outcomes, most of studies demonstrated similar results of UC design TKA with PS or CR, it is consistent with our study results. Multiple factors include geometry, implant size, type of insert, PCL integrity, and gap balancing are associated with AP instability in TKAs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Many studies have compared between TKAs with an UC insert and other design inserts. 9,11 14,31,32 In terms of clinical outcomes, most of studies demonstrated similar results of UC design TKA with PS or CR, it is consistent with our study results. Multiple factors include geometry, implant size, type of insert, PCL integrity, and gap balancing are associated with AP instability in TKAs.…”
Section: Discussionsupporting
confidence: 91%
“…Interest in TKA with UC insert is increasing, some studies underwent biomechanical study about UC design, demonstrated as inferior AP stability in 90 knee flexion state than PS design due to lack of post-cam mechanism. 11,14 Otherwise, one intraoperative study that compared AP stability between UC and PS in respect of 0 , 30 , 60 , and 90 flexion state demonstrated that UC showed greater AP translation in 60 and 90 but similar in 0 and 30 ; this study suggested that implant design if UC or PS had minimal effect on mid-flexion instability. 12 This finding supports our study results that postoperative mid-flexion stability was similar between TKA with UC and PS insert.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Despite the kinematic differences, studies have found equivalent clinical outcomes between PS TKA and UC inserts. 47,49,50,55,56 Some studies have also shown that UC inserts have comparable clinical outcomes to cruciate retaining TKA. 54,5759…”
Section: Ultracongruent Insertsmentioning
confidence: 99%
“…Furthermore, the joint perception and isokinetic performance were similar between UC TKA and PS TKA [52,53]. However, with the use of a navigation system intraoperatively, UC TKA was found to have more sagittal laxity with less femoral rollback and knee flexion than PS TKA [53][54][55]. Unfortunately, the abovementioned studies used native osteoarthritic knees, not knees with PJI after resection.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%